أصول ودلالات السياق المقامي في التراث العربي - جغبوب, صورية (Revues faculté des lettres et des langues; No 16 (2014): مجلة كلية الآداب واللغات)
يعالج هذا المقال فكرة السياق المقامي في التراث العربي؛ حيث نالت هذه الفكرة حظا وافرا من الدراسة في هذا التراث عند الكثير من العلماء على اختلاف مشاربهم؛ فاهتم بها اللغويون في ضبط قواعد الكلام، وكذا البلاغيون في بيان جمالية النصوص الأدبية والأصوليون وعلماء التفسير في معرفة الأحكام وتفسير النص القرآني.    This essay trays to give an idea about the situatianl in the Arabic tradition, this idea was discussed by ma researchers from different areas; it was studied by linguists in the way of giuing the principles and the standards of speech the eloquence persons in showing the aesthetical sides of the texts, the founders and the interpreter in knowing the judgements and the rules in clarifying quran.